Current issues of digitalisation of social and economic systems - N. S. Kozyr (Вестник университета)
The object of the research is the issues of digital transformation, which must be taken into account in the national policy of the Russian Federation for the successful implementation of ambitious national goals of technological development of society and the state. The article analyzes the experience of foreign countries in topical issues (digital agenda; digital government; digital divide), which are defined as an integral part of digitalisation and have mutual influence. The author came to the conclusion that in the digital agenda, only comprehensive measures to improve citizens’ living standards can become effective tools for solving the problem of public resistance to technological development. The successful functioning of digital government is based on nine components of evolutionary development, where the final stage should be the digital ecosystem of the state. The digital divide, which significantly affects the stability of socio-economic systems, is the most difficult issue to focus on when developing roadmaps for technological improvement.